PERLINDUNGAN HUKUM BAGI INVENTOR PICK UP GITAR ELEKTRIK DAN SANKSI TERHADAP PENDUPLIKASIAN INVENSINYA - Alvian Prasetya Putera, Anak Agung; Budi Arsika, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 03, Juni 2014)
Patent occurs in various fields of industry in the form of technology. One of the industries that are the music industry. The technology developed in this music industry is Pick Up Electric Guitar. The purpose of this paper is to explain how the legal protection for the inventor pick up the electric guitar itself and how the sanctions for another party or actors that attempt to duplicate pick up the electric guitar itself. Seen from the object, this paper uses the research methods of approach Normative Law legislation. The sources of law derived from the legal and law books. The conclusion, that all forms of protection against dam inventor sanctions for businesses that duplication pick up the electric guitar set in the the Patent Act.
Keywords: Technology, Music Industry, Inventors Electric Guitar Pickups, Protection